Executive functioning in matrescence and implications for perinatal depression - Ghadimi, T. Roxana; McCormack, Clare (Frontiers in Psychiatry, 2025)
The perinatal period represents a time of profound neurobiological, cognitive, and emotional change. While evidence points to the neuroplasticity of matrescence as adaptive in supporting the transition to motherhood, the perinatal period also entails subjective reports of cognitive difficulty known as “mommy brain” as well as a heightened vulnerability to mental health challenges. The role of cognition in the etiology of postpartum depression is a promising area of investigation into targets for maternal mental health intervention, considering evidence that important cognitive changes occur during the perinatal period, and given that cognitive alterations are key features of mood disorders. Here we review evidence for cognitive plasticity in matrescence, with a particular focus on executive function (EF) given its overlapping significance for adaptation to parenthood, central role in managing the mental load of motherhood, and implications in mood regulation and mood disorders. We also review evidence for EF changes in perinatal depression and major depressive disorder more broadly. Despite the strong association between EF impairments and major depressive disorder, research on EF changes in perinatal depression remains limited. Understanding normative EF changes during this period is essential for better understanding the relationship between EF, perinatal depression, and the mental load of motherhood. Consideration for these cognitive, neurobiological, and psychosocial factors of matrescence is critical for addressing maternal mental health and developing interventions that support parental well-being.